Highly variable hemoglobin-mass changes during successive altitude training camps in world-class female water polo players - Mujika, I.; Tian, R.; Zelenkova, I.; Pyne, D. B. (International Journal of Sports Physiology and Performance, 2025)
Background: The effects of repeated "live high-train high" training camps on total hemoglobin mass (tHBmass) in female team-sport athletes have not been investigated.